THE DEVELOPMENT OF SHARI’AH ACCOUNTING: EPISTEMOLOGY PERSPECTIVE - Alim, Mohammad Nizarul (European Scientific Journal, ESJ, 2014)
The shari’ah accounting has emerged and developed when the shari’ah business has been growth. Shari’ah accounting rests on shari’ah compliance. Development of shari’ah accounting touches fundamental aspect in epistemology such as the concepts of shari’ah transactions which implies shari’ah-based accounting postulates, principles, concepts, and financial reporting. This paper aims to explore the discourses of epistemology in the development of Shari’ah accounting. It will describe the shari’ah principles as an epistemology of Islam. This paper also discusses some challenges facing epistemology in Shari’ah accounting.